Covalent attachment of proteins to solid supports and surfaces via sortase-mediated ligation - Chan, L.; Cross, H.F.; She, J.K.; Cavalli, G.; Martins, H.F.P.; Neylon, Cameron (PUBLIC LIBRARY SCIENCE, 2007)
Background. There is growing interest in the attachment of proteins to solid supports for the development of supported catalysts, affinity matrices, and micro devices as well as for the development of planar and bead based protein arrays for multiplexed assays of protein concentration, interactions, and activity. A critical requirement for these applications is the generation of a stable linkage between the solid support and the immobilized, but still functional, protein.